Mobility in a global city: Making sense of Shanghai's growing automobile-dominated transport culture. (August 2017) - Williams, Matthew; Arkaraprasertkul, Non
Shanghai continues to position itself as the financial capital of the Chinese mainland economy. The concomitant explosion in wealth, the increasing penetration of consumer culture, the in-migration of vast numbers of non-Shanghainese to the city seeking work and the dispersal of the city to the periphery all have significant implications for mobility. This research poses three questions: 1) How do people move around Shanghai? 2) Why do they move in this way? 3) How does this choice of mobility impact on their being and sense of agency? Adopting a qualitative methodology, we approach mobility as a cultural phenomenon and seek to uncover the meanings that car drivers and transit riders attach to mobility and how this impacts their life and their experience of Shanghai. We found that in spite of the fact that Shanghai now has the most extensive metro system in the world, there is a growing materially, culturally and socially embedded automobile culture. The car has a resilient symbolic appeal for the residents of Shanghai. While the automobile is enabling in some routine functions of daily life, collectively it has diminished the agency of people in Shanghai. Congestion, pollution and psychosocial pressure to buy a car portend a socially unsustainable system of mobility. While the metro enables vast numbers of individuals to perform the functions of daily life, it is becoming overcrowded and is associated with the spatial and class-based segregation of people.